Distribution of organically bound tritium (OBT) activity concentrations in aquatic biota from eastern Canada. (November 2019) - Kim, S.B.; Bredlaw, M.; Rousselle, H.; Stuart, M.
Abstract: A survey of eastern Canadian biota was conducted to determine the distribution of activity concentrations of organically bound tritium (OBT). Fish samples were collected from Lake Ontario and the St. Lawrence River in areas continuously receiving inputs of tritiated water (HTO) from operating nuclear power plants, and from Lake Nipissing, a background area. Components of their aquatic environments were sampled. The data collected also provides some insight on how tritium activity concentrations in ambient water influence tissue free water tritium (TFWT) and OBT activity concentrations in biological tissues. Using an ALOKA liquid scintillation system, fish TFWT and OBT were quantified. Fish TFWT averaged 1.6 ± 0.1 Bq/L in Lake Nipissing and 3.1 ± 0.3 Bq/L in Lake Ontario. In contrast, TFWT ranged from 11.1 to 80.8 Bq/L in the St. Lawrence River near the Gentilly-2 Canada Deuterium Uranium (CANDU) site. Fish tissue OBT levels were 4.0 ± 0.4 Bq/L and 5.3 ± 0.2 Bq/L for Lake Nipissing and Lake Ontario, respectively, and between 18.1 and 134.2 Bq/L for CANDU sites. The activity concentrations of TFWT and OBT were reviewed for algae, freshwater mussel and various fish samples collected near Gentilly-2, Pickering and Darlington Nuclear Power Generating Stations. TFWT in aquatic biota was found to correlate with the tritium activity concentrations measured in waters at the time of sampling (TFWT/HTO of ambient water was 0.3–4.3). The OBT concentration factors (OBT/HTO of ambient water) were found to be higher in freshwater mussels (between 17 and 47) compared to algae and fish (0.3–10). These results point to a heterogeneous distribution of biota OBT content in these aquatic ecosystems. It was also noted that all fish and algae samples were found to be within the range of tritium activity concentrations that has been historically measured in the same waters. Values in freshwater mussels were above this range. Highlights: The distribution of activity concentrations of OBT from biota was determined in eastern Canada. The results of TFWT and OBT provide some insight on tritium behaviors in aquatic biota. OBT/TFWT ratio point to a heterogeneous distribution of biota OBT content in these aquatic ecosystems.